High performance work system (HPWS), organisational justice, on-the-job embeddedness and turnover intention among employees at five-star hotels in Malaysia / Mohd Faeez Saiful Bakhtiar - Saiful Bakhtiar, Mohd Faeez (2021)
The hotel industry is largely reliant on the skills and efforts of operational employees. These employees are critical especially in high-end hotels as they are the key to delivering superior quality service experience to the guests. The significance of operational employees in high-end hotels, in addition to the ongoing challenges in retaining them are the primary reasons for this empirical work. Past literature predominantly shows that hotel practicing High-Performance Work System or HPWS; a form of strategic HRM work system is likely to benefit from improved organisational and employee outcomes which include lower turnover rate. In assessing one’s turnover decision, it is valuable to analyse the individual’s perceived organisational justice and on-the-job embeddedness; both are psychological determinants associated with turnover intention. Through quantitative research approach, this study examined the influence of organizational justice (covering distributive, procedural and interactional justice) and on-the-job embeddedness between High Performance Work System (HPWS) and turnover intention among operational hotel employees. A total of 392 usable responses representing rank and file employees from five-star hotels in Kuala Lumpur were successfully analysed using PLS-SEM and Sobel mediation test. On-the-job embeddedness and organisational justice were found to mediate the link between HPWS had turnover intention. Both mediators were positively linked to HPWS and negatively linked to turnover intention. Similar pattern of results were observed for both procedural and interactional justice (organisational justice sub-dimensions), except distributive justice that was negatively and insignificantly linked to turnover intention. This study offered a unique finding where perception of distributive justice does not matter among operational employees which contradict with the existing literature. This research further revealed that the communications as well as performance management and appraisal currently applied were regarded as most perceived agreed practices, whereas compensation and benefits being the least agreeable among all High Performance Work Practices (HPWPs). Findings from this study along with the widespread acknowledgement on the progressive evolution in Human Resource Management (HRM) suggests that research relating to behavioural perspective of strategic HRM theoretical model still has a long future ahead. Also, existing limitations and propositions are presented to guide future research. Results from this study were justified and making relevant theoretical, methodological and practical contributions to the hospitality strategic HRM literature and theories.